Impact of Digital Literacy and Cultural Factors on Online Training for Workforce Productivity among Frontline Workers in India - Verma, Nishtha; Raghuvanshi, Richa; Barthwal, Tripti (International Review of Management and Marketing, 2025)
The study explores the role of digital literacy and cultural factors in shaping the effectiveness of online training among frontline healthcare workers in India. With the rapid digitization of workforce development initiatives, understanding how these two variables influence training outcomes is vital. A quantitative research design was employed, and data were collected from 603 healthcare professionals, including nurses, paramedics, doctors, and community-level workers such as ASHAs, ANMs, and Anganwadi workers. The study used Structural Equation Modeling (SEM) to examine the relationships among digital literacy, cultural factors, online training effectiveness, and workforce productivity. The findings reveal that both digital literacy and cultural compatibility significantly influence the uptake and success of online training programs, which in turn impact employee Productivity. The insights underline the importance of designing culturally sensitive and digitally inclusive training modules for India’s diverse healthcare workforce.